2011
DOI: 10.14214/sf.118
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhization, establishment and growth of outplanted Picea abies seedlings produced under different cultivation systems

Abstract: In forest nurseries seedlings are commonly produced using different cultivation systems which may have a profound effect on the extent of root colonisation by ectomycorrhizal (ECM) fungi and, consequently, on subsequent performance of the outplanted seedlings under field conditions. In this study, we compare effects of bare-root and containerised cultivation systems on mycorrhization, establishment and growth of nursery-produced Picea abies. One hectare experimental plantation was established on poor fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…While the fungus may receive up to 22 % of total plant carbohydrate allocation (Hobbie 2006) and form a stronger sink for C than plant growth during the early establishment of the symbiosis (Menkis et al 2011), there is strong evidence that ECM improve survival, establishment and growth of seedlings in forest plantations over the long term. Lists of the beneficial effects for the plant of ECM partnership include: improved uptake of water and nutrients, particularly nutrients with low diffusion rates or that occur in complex forms; increased root longevity and growth; protection of roots against drought, high temperatures, pathogens, heavy metals, alkalinity and salts; and improved soil aggregation (Davey 1990;Menkis et al 2011).…”
Section: Part Ii: the Ectomycorrhizal Fungus 3 Tree Interaction And Rmentioning
confidence: 99%
“…While the fungus may receive up to 22 % of total plant carbohydrate allocation (Hobbie 2006) and form a stronger sink for C than plant growth during the early establishment of the symbiosis (Menkis et al 2011), there is strong evidence that ECM improve survival, establishment and growth of seedlings in forest plantations over the long term. Lists of the beneficial effects for the plant of ECM partnership include: improved uptake of water and nutrients, particularly nutrients with low diffusion rates or that occur in complex forms; increased root longevity and growth; protection of roots against drought, high temperatures, pathogens, heavy metals, alkalinity and salts; and improved soil aggregation (Davey 1990;Menkis et al 2011).…”
Section: Part Ii: the Ectomycorrhizal Fungus 3 Tree Interaction And Rmentioning
confidence: 99%
“…P i transferred to host tissue in excised beech ECM is through active transport by the sheath hyphae (Bücking and Heyser 2003). Growth responses following seedling inoculation under controlled conditions with beneficial ECM fungi like Pisolithus and Rhizopogon species have been repeatedly observed (Menkis et al 2011). Plant growth responses have been extensively studied using different ECM mushrooms, viz., Tuber, Lactarius, Laccaria, Scleroderma, Cenoccocum, Thelephora, Cantharellus, Paxillus, Amanita, Hebeloma, Suillus, etc.…”
Section: Effect Of Ecm On Growth and Nutrient Uptakementioning
confidence: 99%
“…Plant growth responses have been extensively studied using different ECM mushrooms, viz., Tuber, Lactarius, Laccaria, Scleroderma, Cenoccocum, Thelephora, Cantharellus, Paxillus, Amanita, Hebeloma, Suillus, etc. (Menkis et al 2011). Although ECMs are commonly assumed to enhance water uptake by their hosts, few researchers have addressed this experimentally.…”
Section: Effect Of Ecm On Growth and Nutrient Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings can get mycorrhizal infection already in the nurseries without inoculation (e.g. Menkis et al, 2011). Flykt et al (2008) concluded that the natural mycorrhizal colonisation of Norway spruce in some Finnish nurseries was rather high, 50Á60%, whilst in others it was negligible.…”
Section: Introductionmentioning
confidence: 99%